Ketamine treatment for buprenorphine-precipitated opioid withdrawal: a case report - Ezioma Gbujie; Ezioma Gbujie; Ezioma Gbujie; Lisa Vercollone; Joji Suzuki; Joji Suzuki (Frontiers in Psychiatry)
BackgroundThe presence of fentanyl in the drug supply is thought to contribute to the incidence of buprenorphine-precipitated opioid withdrawal (BPOW) during initiation. Long used as a surgical anesthetic and an analgesic, the utility of ketamine for psychiatric and substance use disorder indications continues to grow. We present a case of intravenous (IV) ketamine use on the general medical floor for the management of BPOW in a hospitalized patient.Case summaryA 72-year-old male presented to the emergency room with new-onset hematuria and was admitted for urological intervention. Hematuria was successfully managed with continuous bladder irrigation over 3 days. Unfortunately, on hospital day two, the patient developed myalgias, restlessness, and later revealed ongoing non-medical use of illicit opioids. The addiction consultation service was consulted on the second day of hospitalization and made a new diagnosis of severe opioid use disorder. Two separate attempts at buprenorphine/naloxone high-dose initiation to treat BPOW were not successful and the second was not responsive to standard symptomatic agents. An IV ketamine 27mg bolus was then administered, with an initial improvement followed by subsequent emergence delirium, which was addressed with IV haloperidol. The patient was eventually stabilized on buprenorphine/naloxone 8mg twice daily prior to discharge.Clinical significanceKetamine may be an effective adjunctive agent in managing opioid withdrawal. Usually restricted to the intensive care unit and emergency department, this case report highlights both the potential and risks of IV ketamine on the general hospital floors. Further research is needed to better understand the safety of using ketamine to manage opioid withdrawal.